EFFECT OF EXCESSIVE SALT CONSUMPTION ON NIGHT’S SLEEP - Fereidoun, Heydarpour; Pouria, Heydarpour (Pakistan Journal of Physiology, 2018)
Background: Low sodium chloride intake may play a role in the treatment of insomnia and tension states. The objective of this study was to evaluate the effect of excessive amount of salt consumption on night’s sleep. Methods: Twenty volunteer students having no sleep problems were selected for this study. Five nights before salt consumption, the volunteers recorded the time of going to bed and the time of rising next morning and the quality of night’s sleep. On the 6th day, each volunteer consumed 0.5 g salt per 10 Kg of body weight at 8.00 PM and filled a questionnaire with queries on the time of going to bed and the time of rising next morning, depth of sleep, frequency of awakening at night, presence of any sleep disturbances, amount and times of drinking water during the night, and general condition in the next day. Results: Salt consumption delayed the time of going to bed and awakened the subjects earlier. During sleep, students awakened several times and they had 2–3 hours of sleep disturbances during that night. The normal pattern of sleep was disrupted and the depth of sleep was decreased. Students repeatedly got up to drink water. On the next day of salt consumption, students felt drowsy and fatigued and were not satisfied with last night’s sleep. Conclusion: Excessive amount of salt consumption could affect the pattern and duration of sleep. Role of a healthy diet in habitual sleep duration represents a largely unexplored pathway linking sleep and health. Pak J Physiol 2014;10(3-4):6–9